A autonomia privada solidária e a despedida coletiva no direito do trabalho - Costa, Jefferson Alexandre da (2017)
One of the great issues of capitalism and the globalized market is the incidence of workers' collective dismissal, whose effects reach, beyond the worker himself, his family and the society. Changes in the economic, technological or structural situation of companies are directly related to the reasons for collective dismissals, however, an adequate evaluation of the circumstances is not always verified, nor are alternatives sought to avoid the termination of the contracts, which violates several fundamental rights. Labor relations are established through labor contracts, which has been developed for a long time within the scope of the autonomy of the will and legal positivism. Modern social relations evolve rapidly, while legislative formalism renders legislation unable to keep pace with social dynamism, strengthening contract use. The classic concept of contract is linked to the pacta sunt servanda, which enforces compliance with the agreement, ignoring possible imbalances caused by external circumstances and which may hinder compliance with the contract. After the Second World War, the sense of positivist Law and distant from morality went through profound changes, reinforced by the Universal Declaration of Human Rights, that began to consider the human person as the center of the legal system, also fostering the phenomenon of constitutionalisation and functionalization of Private Law. This set of modifications is contained in the paradigm of legal post-positivism, which advocates the application of constitutional principles in private relations, including labor relations, from pre-contractual to post-contractual phases. The autonomy of the will gives way to the private solidarity autonomy, making every contractual relation respect the dignity of the human person, as well as the objective good-faith and its associated duties, the information duty, solidarity, among other rights and principles. In this context, the present academic work approaches two issues of salient importance for the treatment of contemporary labor relations: the direct and immediate application of fundamental rights and the private solidarity autonomy in labor relations. For that, the hypothetical-deductive method was adopted, associated with the technique of bibliographical research of national and foreign works. The justification is linked to the fact that the doctrine and the jurisprudence have not yet adopted the private solidarity autonomy as a paradigm of contractual relations in the scope of Labor Law. Although it has been the target of the Labor Reform, the regulation of collective dismissal in Brazil was not adequate to meet social needs and interests. The objective is to point out that the private solidarity autonomy is capable of ensuring the effectiveness of fundamental rights and foster the solidarity and cooperative attitude among workers and employers, suggesting the conclusion that the application of the private solidarity autonomy has sufficient conditions to avoid or minimize the impacts of collective dismissal, as well as to prevent abuses or violations of rights